Antibiotic resistance and plasmid profiling of Vibrio spp. in tropical waters of Peninsular Malaysia - You, K.G.; Bong, C.W.; Lee, C.W. (Kluwer (now part of Springer), 2016)
Vibrio species isolated from four different sampling stations in the west coast of Peninsular Malaysia were screened for their antimicrobial resistance and plasmid profiles. A total of 138 isolates belonging to 15 different species were identified. Vibrio campbellii, V. parahaemolyticus, V. harveyi, and V. tubiashii were found to predominance species at all stations. High incidence of erythromycin, ampicillin, and mecillinam resistance was observed among the Vibrio isolates. In contrast, resistance against aztreonam, cefepime, streptomycin, sulfamethoxazole, and sulfonamides was low. All the Vibrio isolates in this study were found to be susceptible to imipenem, norfloxacin, ofloxacin, chloramphenicol, trimethoprim/sulfamethoxazole, and oxytetracycline. Ninety-five percent of the Vibrio isolates were resistant to one or more different classes of antibiotic, and 20 different resistance antibiograms were identified. Thirty-two distinct plasmid profiles with molecular weight ranging from 2.2 to 24.8 kb were detected among the resistance isolates. This study showed that multidrug-resistant Vibrio spp. were common in the aquatic environments of west coast of Peninsular Malaysia.